Uncovering de novo polyamine biosynthesis in the gut microbiome and its alteration in inflammatory bowel disease - Xinwei Li; Xia Xiao; Shengnan Wang; Biyu Wu; Yixuan Zhou; Pan Deng (Gut Microbes)
Polyamines are important gut microbial metabolites known to affect host physiology, yet the mechanisms behind their microbial production remain incompletely understood. In this study, we developed a stable isotope-resolved metabolomic (SIRM) approach to track polyamine biosynthesis in the gut microbiome. Viable microbial cells were extracted from fresh human and mouse feces and incubated anaerobically with [U-13C]-labeled inulin (tracer). Liquid chromatography-high resolution mass spectrometry analysis revealed distinct 13C enrichment profiles for spermidine (SPD) and putrescine (PUT), indicating that the arginine-agmatine-SPD pathway contributes to SPD biosynthesis in addition to the well-known spermidine synthase pathway (PUT aminopropylation). Species differences were observed in the 13C enrichments of polyamines and related metabolites between the human and mouse microbiome. By analyzing the fecal metabolomics and metatranscriptomic data from an inflammatory bowel disease (IBD) cohort, we found significantly higher polyamine levels in IBD patients compared to healthy controls. Further investigations using single-strain SIRM and in silico analyses identified Bacteroides spp. as key contributors to polyamine biosynthesis, harboring essential genes for this process and potentially driving the upregulation of polyamines in IBD. Taken together, this study expands our understanding of polyamine biosynthesis in the gut microbiome and will facilitate the development of precision therapies to target polyamine-associated diseases.